Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The following result must be well known, but it is instructive to give it here in view of the recent posts Y= X+N what is E(X|Y=y) and http://mathoverflow.net/questions/47168/ex-1-x-1-x-2-where-x-i-are-integrable-independent-infinitely-divisib/47204#47204. This is also an interesting exercise in its own right.

Suppose that $X_1$ and $X_2$ are independent ${\rm Gamma}(c_i,\lambda)$ rv's, meaning that $X_i$, $i=1,2$, has density function $f_{X_i } (x) = \lambda ^{c_i } {\rm e}^{ - \lambda x} x^{c_i - 1} /\Gamma (c_i )$, $x > 0$ ($c_i$ are positive constants, $\Gamma$ is the gamma function). Show that $$ {\rm E}(X_1 | X_1 + X_2 = z) = \frac{{c_1 }}{{c_1 + c_2 }} z. $$

share|improve this question
    
Of course, you are not allowed to apply the general principle indicated in the aforementioned posts (concerning infinitely divisible distributions). –  Shai Covo Nov 24 '10 at 10:17

2 Answers 2

First of all, we note that $X_1 + X_2 \sim {\rm Gamma}(c_1 + c_2 , \lambda)$. Given that $X_1 + X_2 = z$, $X_1$ cannot exceed $z$. We can thus find ${\rm E}(X_1|X_1+X_2=z)$ as follows. $$ {\rm E}(X_1|X_1 + X_2 = z) = \int_{0}^z {xf_{X_1|X_1 + X_2} (x|z)\,{\rm d}x} = \int_{0}^z {x\frac{{f_{X_1} (x)f_{X_1 + X_2|X_1} (z|x)}}{{f_{X_1 + X_2} (z)}}\, {\rm d}x}. $$ Noting that $f_{X_1 + X_2|X_1} (z|x) = f_{X_2} (z-x)$, it follows after some algebra and a change of variable that the right-hand side integral is equal to $$ z\frac{{\Gamma (c_1 + c_2 )}}{{\Gamma (c_1 )\Gamma (c_2 )}}\int_0^1 {x^{c_1 } (1 - x)^{c_2 - 1} \,{\rm d}x} = z\frac{{\Gamma (c_1 + c_2 )}}{{\Gamma (c_1 )\Gamma (c_2 )}}{\rm B}(c_1 + 1,c_2 ), $$ where ${\rm B}(a,b) = \int_0^1 {t^{a - 1} (1 - t)^{b - 1} \,{\rm d}t}$ is the beta function. Finally, from the alternative form ${\rm B}(a,b) = \frac{{\Gamma (a)\Gamma (b)}}{{\Gamma (a + b)}}$ followed by $\Gamma (p+1) = p \Gamma (p)$, we obtain $$ {\rm E}(X_1|X_1 + X_2 = z) = \frac{{c_1 }}{{c_1 + c_2 }} z. $$

share|improve this answer

another way to get this result is to first recall that $S := X_1+X_2$ and $R := X_2/X_1$ are independent. [this is well-known and can be proved by the usual method of derived distributions for two random variables. the mapping $(X_1,X_2) \to (R,S)$ is 1-1 and easily inverted. this is a standard example or exercise in many intro probability and math stat books - such as here.]

then, noting that $\frac{X_1}{X_1+X_2} = \frac{1}{1+R}$,

$$ {\mathrm E}\{ X_1 | S\} = {\mathrm E}\{ \frac{S}{1+R} | S\} = S\kern1pt {\mathrm E}\{ \frac{1}{1+R} | S\} = S\kern1pt{\mathrm E}\frac{1}{1+R}. \kern10pt (1)$$

the last equality in (1) follows from independence. also, [on repeating the argument - or just taking unconditional expectations in (1)],

$$ c_1 = {\mathrm E}X_1 = {\mathrm E}\frac{S}{1+R} = {\mathrm E}\frac{1}{1+R}\kern2pt {\mathrm E}S = {\mathrm E}\frac{1}{1+R}(c_1+c_2),$$

so

$$\kern84pt {\mathrm E}\frac{1}{1+R} = \frac{c_1}{c_1+c_2}, \kern84pt (2)$$

which can be plugged into (1) to get the result.

[btw, (2) says that

$${\mathrm E}\frac{X_1}{X_1+X_2} = \frac{{\mathrm E}X_1}{{\mathrm E}(X_1+X_2)},$$

a relation which, in general, is a fond wish of students in an intro prob or stats course - and perhaps the instructors too.]

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.